Impacts of the COVID-19 pandemic on food security and food consumption: Preliminary insights from the gulf cooperation council region - Tarek Ben Hassen (15742605) (2022)
As the coronavirus pandemic spreads, measures to contain it—such as home confinement, social isolation, closure of businesses and educational institutions, and remote work—have affected everyday life. Further, some voices were worried about these measures’ psychological, social, and economic impacts on food-related activities and practices. These impacts are presumably context-specific and differ from one region to another. In this regard, the example of the Gulf Cooperation Council (GCC) region, a group of high-income and food-secure countries, is particularly intriguing. This narrative review aims to explore the psychological and socio-economic effects of the COVID-19 pandemic on food-related activities (e.g., food procurement, preparation, and consumption) in the GCC area. The review suggests that while the changes in lifestyle brought on by the lockdown/quarantine measures generated concern, boredom, sadness, stress, and anxiety also in the GCC region, the impacts of these negative emotions on food-related activities have been rather limited. Indeed, the pandemic impacted the consumer-food interaction but did not boost panic buying and hoarding in the region. Furthermore, the high purchasing power of the population mitigated the economic impacts of the pandemic and its adverse effects on food and nutrition security in the region. Other Information Published in: Cogent Social Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311886.2022.2064608